New records of insect and mite pests of spice crops in Andaman Islands, India - RANGANATH, K VEENAKUMARI, PRASHANTH MOHANRAJ, H R (Journal of Spices and Aromatic Crops, 1994)
Eighteen species of insects and one species of mite are reported for the first time from seven spice crops viz., cinnamon, clove, black pepper, nutmeg, curry leaf, chillies and turmeric, from Andaman and Nicobar Islands, India.